(untitled) (Bangladesh Journal of Nuclear Medicine, 2019)
Objective: Gated SPECT myocardial perfusion imaging (GSMPI) is a preferred modality for non invasive assessment following coronary revascularization (CR) of both symptomatic and asymptomatic patients. This study was conducted to observe the impact of GSMPI results on further management of patients who after CR had underwent GSMPI at National Institute of Nuclear Medicine and Allied Sciences (NINMAS). Patients and methods: Record files of GSMPI of all patients who underwent GSMPI over a period of 31 months from June 2011 to December 2013 at NINMAS for assessment of perfusion after CR were selected from the Nuclear Cardiology Divisional archive of patient studies in order to retrieve their clinical and demographic data including the contact numbers. The results of GSMPI scan were categorized as normal scan (NS) and perfusion defect (PD) which included reversible and/or fixed PD. All the contact numbers were called up by a nuclear medicine physician who conducted a semi-structured telephonic interview either with the patients or with a concerned family member. Management strategies adopted after GSMPI were categorized as conservative (CM) and interventional (IM).Cramer’s V (φc) test were done to find strength of relation among patients’ symptoms, scan findings and management strategies. Results: Follow up data of 55 patients (54M, 1F) among 68 (66M, 2F) were available who underwent MPI for the purpose of post CR assessment. MPI was performed in between six months to 13 years after CR (mean 43.8 ± 48.2 months). Categorically 33 patients had percutaneous transluminal coronary angioplasty (PTCA) with stent, 16 patients had coronary artery by-pass grafting (CABG) and 6 patients had both CABG & PTCA. There were 38PD (27symptomatic) and 17NS(12 symptomatic).Since all patients (n=12) who had fixed PD were symptomatic, a strong relation was found between being symptomatic and fixed perfusion defect (φc> 0.3). Symptoms were found to be weakly related with reversible PD i.e. ischemia (φc< 0.2). Management strategies were conservative in 44 (30 symptomatic and 28 PD) and interventional in 11 (nine symptomatic and 10 PD). Management strategies were found to be weakly related with symptoms (φc< 0.2) but moderately related with perfusion status (φc = 0.24). Conclusions: While symptoms were observed to be poorly related with perfusion status following CR, GSMPI guided to choose further interventional management strategies with rationality in lower proportion of patients. Bangladesh J. Nuclear Med. 22(1): 30-35, Jan 2019